Opaque indifference, trust and service provider success in offshore business process outsourcing - Wreford, John; Penter, Kevan; Pervan, Graham; Davidson, Fay (ACIS, 2011)
Business Process Outsourcing (BPO) is the delegation of one or more business processes to an external service provider (which may be an offshore captive centre or a third party). The focus of most BPO research has been the cost reductions delivered by third party providers of BPO services in offshore locations in India, Eastern Europe and elsewhere, and there has been little research on captive centres or the satisfaction of the end customer. This paper introduces the new concept of “opaque indifference” (where the end-user is indifferent to where or by whom the service is provided) and its association with customer satisfaction and BPO success. A model incorporating these concepts is introduced and investigated via four in-depth longitudinal case studies.